2004
DOI: 10.1124/jpet.104.071571
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Cyclooxygenase System on Doxorubicin-Induced Functional Multidrug Resistance 1 Overexpression and Doxorubicin Sensitivity in Acute Myeloid Leukemic HL-60 Cells

Abstract: Multidrug resistance (MDR), a challenge in treating childhood acute myeloid leukemia (AML), is frequently associated with decreased drug accumulation caused by multidrug transporter MDR1. Doxorubicin, an important anti-AML drug, is a known MDR1 substrate and inducer. Its cytostatic efficacy is thus limited by MDR1 overexpression. A recent study demonstrated cyclooxygenase-2-dependent, prostaglandin E 2 (PGE 2 )-mediated regulation of mdr1b expression in primary rat hepatocyte cultures. Cyclooxygenase-2 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 32 publications
5
33
2
Order By: Relevance
“…A growing body of evidence has demonstrated that NSAIDs and COX-2-selective inhibitors enhance the cytotoxic action of certain chemotherapeutic drugs in a variety of cancer cells (Draper et al, 1997;Duffy et al, 1998;Roller et al, 1999;Awara et al, 2004;O'Connor et al, 2004;Puhlmann et al, 2005;Zatelli et al, 2005Zatelli et al, , 2007Zrieki et al, 2008). In agreement with these findings, our results show that the NSAID indomethacin and the COX-2-selective inhibitor SC236 sensitize human esophageal squamous cell carcinoma cells (HKESC-1 and HKESC-2) to the cytotoxic action of doxorubicin.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…A growing body of evidence has demonstrated that NSAIDs and COX-2-selective inhibitors enhance the cytotoxic action of certain chemotherapeutic drugs in a variety of cancer cells (Draper et al, 1997;Duffy et al, 1998;Roller et al, 1999;Awara et al, 2004;O'Connor et al, 2004;Puhlmann et al, 2005;Zatelli et al, 2005Zatelli et al, , 2007Zrieki et al, 2008). In agreement with these findings, our results show that the NSAID indomethacin and the COX-2-selective inhibitor SC236 sensitize human esophageal squamous cell carcinoma cells (HKESC-1 and HKESC-2) to the cytotoxic action of doxorubicin.…”
Section: Discussionsupporting
confidence: 88%
“…The basal PGE 2 level released by HKESC-1 cells was 332 pg/ml, or approximately 10 Ϫ3 M (data not shown). Moreover, it has been reported that PGE 2 at the concentration of 3 g/ml (8.5 M) neutralized the enhancing effect of the COX-2 selective inhibitor meloxicam on the cytotoxic action of doxorubicin in acute myeloid leukemia HL-60 cells (Puhlmann et al, 2005). Therefore, PGE 2 at concentrations ranging from 10 Ϫ3 to 10 M were used in our study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, it has been reported that COX-2 modulates ABC transporter expression and is involved in the development of the MDR phenotype. A correlation between expression of COX-2 and MDR1 was found in breast cancer (Ratnasinghe et al, 2001), hepatocellular carcinoma (Fantappiè & R, 2002 ), and acute myeloblastic lymphoma (Puhlmann et al, 2005). Previously, we demonstrated that induction of COX-2 expression could increase ABCG2 activity (mitoxantrone efflux) in breast cancer cell lines .…”
Section: Introductionmentioning
confidence: 90%